LA GESTION DE LA DIVERSITE CULTURELLE PAR LES CHEFS D'ETABLISSEMENT REVUE DE LA LITTERATURE - Bauer, Stéphanie; Akkari, Abdeljalil (Revista Educação e Políticas em Debate, 2015)
Contemporary education systems need to address increasing Cultural diversity of students and the need to a change of perspective. From a problem to solve, cultural diversity can become an opportunity to improve learning. This article presents a synthesis of literature on the role of school principals in the management of cultural diversity. The academic literature on this issue is very heterogeneous. We present the main theoretical and conceptual debates. The notion of social justice appears to represent an innovative concept likely to destabilize unequal power relations between groups. The text discusses the professionalization of principals. This article highlights a tension between two visions of school leadership in the management of cultural diversity: a vision linked to critical pedagogy that develops multicultural education as a means to promote social justice and transformation of school structures. On the other side, an approach centered on management of education with a more focused approach towards measurable learning outcomes and greater control of the cost of education.